Controlador de temperatura uniforme - Seidel, Tcharley Alexsander (2012)
Temperature control is often required in some processes. In the middle factory, usually, there are devices known as temperature controllers that have a control on the output type 0 and 1 (on / off). However, this type of control is not useful in some cases where the function of the load and the critical temperatures are uniform and has a continuous control and not simply on / off. This work aims at the development of a power controller that performs automatic temperature control of maternity pens of pigs, performing a gradual variation of the power transferred to the load, and consequently a uniform temperature control.